2006
DOI: 10.1016/j.jmhg.2006.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Sex and gender differences in pain: a selective review of biological and psychosocial factors

Abstract: Evidence suggests that there are important differences between men and women with respect to the perception and experience of pain. The objective of this review is to provide a general overview of this area and to explore potential mechanisms for such differences. It will focus on a range of different types of evidence including experimental studies, epidemiology, as well as more clinically orientated treatment investigations. Some of the biological, psychological and social factors thought to help understand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0
2

Year Published

2008
2008
2011
2011

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 65 publications
1
49
0
2
Order By: Relevance
“…The difference would appear to be underpinned by biological, psychological and social factors. 74 Piira et al 75 observed that during vaccination of 4-month-old children, parents made significantly more coping-promoting statements and generally talked more to female infants than male infants. These data offer explanation for the genesis of the well documented [76][77][78] sex-difference in gender role expectations in pain perception, with masculinity conferring stoicism and femininity more sensitivity.…”
mentioning
confidence: 99%
“…The difference would appear to be underpinned by biological, psychological and social factors. 74 Piira et al 75 observed that during vaccination of 4-month-old children, parents made significantly more coping-promoting statements and generally talked more to female infants than male infants. These data offer explanation for the genesis of the well documented [76][77][78] sex-difference in gender role expectations in pain perception, with masculinity conferring stoicism and femininity more sensitivity.…”
mentioning
confidence: 99%
“…There is evidence that men and women show different responses to pain, and to pharmacological and non-pharmacological treatment approaches [22], and that there is a difference in how the two sexes centrally process pain [23].…”
Section: Discussionmentioning
confidence: 99%
“…The stoma bag appliance was not removed. Disabil Rehabil Downloaded from informahealthcare.com by Thomas Jefferson University on 04/09/15 For personal use only.severe disability (RMDQ[16][17][18][19][20][21][22][23][24]. The greatest agreement among the participants for the 24 items in the RMDQ was "I change position frequently to try and get myself comfortable" (true: n = 17) and "I stay in bed most of the time because of my back" (false: n = 15, true: n = 2).…”
mentioning
confidence: 99%
“…We found that the overall differences in cortisol levels between patient and control groups were largely due to hypocortisolism in male patients. While it is well established that pain-related conditions are more prevalent in females (Berkley 1997;Mogil and Chanda 2005) with increased sensitivity to pain (Keogh and Herdenfeldt 2002;Keogh 2006), endocrine-related mechanisms underlying sex differences in pain have not been systematically addressed and few human studies have examined sex-related dimorphism in the neuroendocrinology of chronic pain. In one of the few studies to examine sex effects in pain patients, Nater et al (2008a) reported a difference in the morning profile of cortisol, where female CFS patients had a significantly lower cortisol profile than female controls, but no difference was observed in corresponding groups of males.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, while the influence of sex is considered to be important within the pain context (Unruh 1996;Berkley 1997;Holdcroft and Berkley 2005;Keogh 2006;Bernardes et al 2008), sex differences in endocrine functioning are rarely considered directly in pain. For example, there are sex differences in pain prevalence rates, analgesic use (Antonov and Isacson 1998), and different responses to pain management approaches (Fillingim 2002;Keogh et al 2005), and these effects tend to be more pronounced in female patients.…”
Section: Introductionmentioning
confidence: 99%